Travelling Girlhood: Feminist Discourses as Narrative Resources for the American Adaptation of the Norwegian High-School Drama SKAM - Dag Skarstein; Synnøve Skarsbø Lindtner (International Journal of Young Adult Literature, 2022)
In the American adaptation of the Norwegian youth drama SKAM (2015-2017), the translation of feminist discourse informing the plot shifts the conflict from a social, political, and democratic level to a question of liberation from within. This shift – from the familiarized inter-relational conflict of filmic melodrama to a conflict within the protagonist’s inner landscape – comes with some interconnected dramaturgical implications that change the invited audience’s opportunities to make sense of the plot at the same time as they complicate the interpretation process. Drawing particularly on theories of melodrama and youth fiction, our analysis indicates that the conflict level might particularly problematize the issue of engagement when the medium is filmic.